Pemberdayaan Masyarakat dalam Upaya Pencegahan DBD dan Stunting di Kelurahan Sungaiselan 2024 - Fajrianti, Gita; Murniani , Murniani; Widiya , Widiya; Maulina, Andini; Suryanto, Hanif Adzany; Sari, Wanda Novita; Amanda, Nadia; Sintia, Tiara; Fauzi, Miftahul (Jurnal Pemberdayaan Umat, 2025)
Purpose: Knowing the health conditions and helping the community in efforts to improve optimal health levels in Sungaiselan Village, Sungaiselan District, Central Bangka Regency. Methodogoly/approach: The methods used are in the form of health education and active participation, namely the target group participates in the activities. This activity was carried out to identify health problems in Sungaiselan Village using the Delbecq method and a survey method with a sample of 95 people. Results/findings: Based on the results of the Delbecq method and the survey method conducted in Sungaiselan Village by identifying three priority health problems, the results obtained were a lack of temporary waste disposal sites (TPS), a high number of stunting cases, and a high number of dengue fever cases. Conclusions: The work program that has been implemented includes the construction of a pilot Temporary Waste Disposal Site (TPS) for organic and inorganic waste, a PMT cooking demonstration of moringa leaf chicken nuggets, socialization on stunting, waste, and dengue fever, as well as community service activities such as Posyandu and mutual cooperation. Limitations: This community service activity has time limitations. Contribution: The community is expected to be able to increase their awareness in improving their health status and the government needs to facilitate the needs required by the community in improving the health status of the community, especially in Sungaiselan Village.